PENGARUH KEADILAN ORGANISASI, LINGKUNGAN KERJA FISIK, DAN KOMPENSASI TERHADAP LOYALITAS KARYAWAN PDAM KABUPATEN PONOROGO - Selly Damayanti; Edi Santoso; Fery Setiawan (Gapenas Publisher, 2022)
This study aims to determine the effect of Organizational Justice, Physical Work Environment, and Compensation on Employee Loyalty of PDAM Ponorogo Regency. The method used in this study uses quantitative methods. The data collection in this study is primary data obtained from distributing questionnaires. The sample in this study were 50 respondents with a sampling technique using a saturated sampling technique. The testing stages used include instrument testing, coefficient of determination test and hypothesis testing. The analysis used in this study is multiple linear regression analysis. The results of this study indicate that: (1) Organizational justice has a positive and significant effect on employee loyalty, as evidenced by the t-count value of 2.305 > 2.012 t table, while the significant value is 0.002 <0.05. (2) The physical work environment has a positive and significant effect on employee loyalty, as evidenced by the t-count value of 2.765 > 2.012 t table, while the significant value is 0.008 <0.05. (3) Compensation has no significant effect on employee loyalty, as evidenced by the t-count value of 1.692 < 2.012, while the significant value is 0.098 > 0.05. (4) Organizational justice, physical work environment and compensation simultaneously have a positive and significant effect on employee loyalty as evidenced by the calculated F value of 5.467 > F table 2.81 and the significant value obtained is 0.003 < 0.05. PDAM Ponorogo Regency is expected to be able to improve the fairness of its organization, the goal is that the quality of human resources in the company continues to run well. In order to increase employee loyalty, companies must pay more attention to employee comfort in terms of cleanliness and tidiness of the physical environment in the workplace. Furthermore, to make employees feel loyal in terms of compensation, it can be added by giving bonuses to employees who have good performance in order to further increase employee loyalty in the company